Evaluation of Educational Environment of Residents of Internal Medicine Based on DRECT Questionnaire at Shiraz University of Medical Sciences Iran in 20142015: A Step towards Group Accreditation - Ali Reza Mogheli; Zohreh Esmaeilzadeh; Javad Kojuri (Kerman University of Medical Sciences, 2016)
Background & Objective: Evaluation of the clinical training environment should be considered as an integral component of an optimal learning environment Therefore the purpose of this study was to evaluate the educational environment of residents at Shiraz University of Medical Sciences Iran based on DRECT (Dutch Residency Educational Climate Test) questionnaire toward educational group accreditation in 20142015 Methods: This mixedmethod study was conducted in two phases The statistical population consisted of all residents in the field of internal medicine (n = 50) The first phase of the present study was performed quantitatively and using DRECT questionnaire The second phase of the study was performed a qualitatively through semistructured interviews with the target group The face validity and reliability of the questionnaire were approved using the views of 5 educational experts and Cronbachs alpha (α = 090) respectively The collected data were analyzed using Pearson coefficient and independent ttest in SPSS software Results: The results of this study demonstrated a meaningful correlation between the fields of professors role formal education guiding and evaluation and decision making for patients treatment The highest correlation was related to the two fields of formal education and decision making for patients treatment (P = 0001) and the least correlation was related to professors role and formal education (P = 0009) In qualitative analysis the strengthens of the group were regular attendance of classes morning reports and planning The weaknesses included revising the educational environment high load of clinical work high number of shifts little amount of time for theoretical studying and lack of attention to specialty skills Conclusion: According to the results the head of educational groups should move toward improving the quality of education in terms of residents cooperation and team work